2021
DOI: 10.48550/arxiv.2112.11714
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Time Perception Control and Regulation in VR Environment

Abstract: To adapt to different environments, human circadian rhythms will be constantly adjusted as the environment changes, which follows the principle of survival of the fittest. According to this principle, objective factors (such as circadian rhythms, and light intensity) can be utilized to control time perception. The subjective judgment on the estimation of elapsed time is called time perception. In the physical world, factors that can affect time perception, represented by illumination, are called the Zeitgebers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…found that present hedonism is linked with a faster passage of the last week; the past negative perspective is related to time pressure; a future perspective is related to a general faster passage of time. And, individuals experience the passage of time differently at different time periods ( 97 ). Specifically, the internal clock ran relatively faster when the circadian oscillation of body temperature was on the rise and relatively slower on the declining portion of the temperature curve ( 98 ).…”
Section: Psychological Time Characteristics In Patients With Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…found that present hedonism is linked with a faster passage of the last week; the past negative perspective is related to time pressure; a future perspective is related to a general faster passage of time. And, individuals experience the passage of time differently at different time periods ( 97 ). Specifically, the internal clock ran relatively faster when the circadian oscillation of body temperature was on the rise and relatively slower on the declining portion of the temperature curve ( 98 ).…”
Section: Psychological Time Characteristics In Patients With Depressionmentioning
confidence: 99%
“…More BTP individuals exhibited more pronounced morning preference (48). Moreover, these two aspects tend to be personal traits, which can affect time perception and passage of time (14,(96)(97)(98)(99)(100). Time perception and passage of time both reflect the subjective feeling of time.…”
Section: The Relationship Between the Four Aspects Of Psychological Timementioning
confidence: 99%